High performance thermoplastic resins and their composites - Béland, Sylvie (Noyes Data Corp., 1990)
Describes developments in thermoplastic resins and their composites, and assesses the benefits and limitations of emerging materials for aerospace and other applications. Discussion includes the performance of neat and continuous fiber reinforced thermoplastic resins in terms of their properties. Also provides information on environmental and chemical resistance.